Political risk and portfolio performance: Implications for Shariah-compliant ‎investors - RAZA, WAJID (International Journal of Islamic Economics and Governance, 2023)
The COVID-19 pandemic has forced the Malaysian economy into a recession, with GDP plummeting to negative growth for the first time since the 1998 Asian Financial Crisis. Fiscal and monetary tools are inevitable during this crisis. Businesses have been forced to close shops due to a series of Movement Control Orders (MCO), resulting in massive layoffs and a rise in the unemployment rate, which is a red flag for the economy. On the other hand, zakat has emerged as a poverty alleviation tool in the Islamic economy landscape and is particularly relevant during an economic crisis. However, there is a lack of literature discussing the impact of macroeconomic indicators on zakat. Therefore, this study was conducted to examine whether the unemployment rate explains the trend in zakat collection. Time series data from the period between 2006 and 2020 was utilized, and linear regression analysis was conducted. An interesting finding is that the zakat collection trend by State Islamic Religious Councils (SIRCs) and the movement of the unemployment rate are not statistically significant. This indicates that zakat collection is not affected by high unemployment in the labor force market and remains strong even during an economic slump, thanks to increased digitalization efforts and FinTech adoption.